"It's not really worth my while": understanding contextual factors contributing to decisions to participate in community aphasia groups. Issue 9 (24th April 2019) - Lanyon, Lucette; Worrall, Linda; Rose, Miranda
Abstract: Purpose: Community aphasia groups represent a formalised opportunity for social participation. The potential barriers and facilitators to accessing and maintaining group participation remain poorly understood. The aim of this study was to explore environmental and personal factors contributing to community aphasia group participation. Methods: A framework analysis (FA) was used to analyse the semi-structured interview data from 22 current and past members of community aphasia groups. Results: People with aphasia weigh up the benefits of group participation in the context of a range of personal and environmental factors. These include personal coping mechanisms, perceptions of existing social support as well as the practicalities of accessing the group. Conclusions: Understanding factors that contribute to participation experiences is critical to ensure that, people with aphasia are well supported to access and engage in community aphasia groups. This study found that people may be more able to participate when they are accepting of the chronic nature of the aphasia, when they identify tangible benefits to participation, and when they have easy access to the group. This suggests a role for speech pathologists to recognise critical periods of need and support people with aphasia and their significant others to access and engage in group services. Implications for Rehabilitation: Critical stages exist when people with aphasia may feel more ready and able to participate in community aphasia groups. These critical stages include an acceptance of the chronic nature of aphasia, as well as a desire to make positive change. There is a need for clinicians to minimise barriers to participation early in the therapeutic relationship. Proliferation of community aphasia groups will function to alleviate environmental barriers associated with poor public awareness of groups and group accessibility.